Investigation of Anticholinesterase Activity of a Series of Salvia Extracts and the Constituents of Salvia staminea - TOPÇU G.; KOLAK U.; Ozturk M.; Boga M.; Hatipoglu S. D.; BAHADORI F.; Culhaoglu B.; Dirmenci T. (My University, 2013)
In continuation of our studies on the genus Salvia fourteen alcoholic extracts of Salvia species were evaluated for their anticholinesterase activity. Among them, the most active extract at 200 mu g/mL was found to be S. staminea with the inhibition of 55.17 and 79.75% against enzymes AChE and BChE, respectively. Pure isolated compounds from S. staminea were investigated for anticholinesterase activity at 200 mu M, and the abietane diterpenoids ferruginol and taxodione were found to be the most promising isolates, which were then further investigated at five different concentrations, and both diterpenoids exhibited high activity, particularly against BChE enzyme with IC50 values of 7.73 and 10.52 mu M, respectively. Salvia chrysophylla and Salvia poculata extracts also exhibited moderate anticholinesterase activity.
Keywords: Eczacılık; Temel Eczacılık Bilimleri; Yaşam Bilimleri; Kimya; Biyokimya; Sağlık Bilimleri; Temel Bilimler; Pharmacology and Therapeutics; Basic Pharmaceutics Sciences; Life Sciences; Chemistry; Biochemistry; Health Sciences; Natural Sciences; Kimya Tıbbi; Temel Bilimler (Sci); Farmakoloji ve Eczacılık; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (Life); Chemistry Medicinal; Natural Sciences (Sci); Pharmacology & Pharmacy; Pharmacology & Toxicology; Life Sciences (Life); Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Chemistry (miscellaneous); General Chemistry; Physical Sciences